How to help small farmers in Bangladesh - Brammer, Hugh. (Dhaka, Bangladesh : University Press, 2002)
Revised and up-dated edition of a report prepared for the Food and Agriculture Organization of United Nations.
Includes bibliographical references and index.
BIED
Keywords: Small Farmers Development Project (Bangladesh).; Farms, Small -- Bangladesh; Agriculture and state -- Bangladesh